Scalable Production of Equine Platelet Lysate for Multipotent Mesenchymal Stromal Cell Culture - Hagen, A.; Lehmann, H.; Aurich, S.; Bauer, N.; Melzer, M.; Moellerberndt, J.; Patané, V.; Schnabel, C. L.; Burk, J. (Frontiers in Bioengineering and Biotechnology, 2021)
Translation of multipotent mesenchymal stromal cell (MSC)-based therapies is advancing in human and veterinary medicine. One critical issue is the in vitro culture of MSC before clinical use. Using fetal bovine serum (FBS) as supplement to the basal medium is still the gold standard for cultivation of many cell types including equine MSC. Alternatives are being explored, with substantial success using platelet lysate-supplemented media for human MSC. However, progress lags behind in the veterinary field. The aim of this study was to establish a scalable protocol for equine platelet lysate (ePL) production and to test the ePL in equine MSC culture. Whole blood was harvested into blood collection bags from 20 healthy horses. After checking sample materials for pathogen contamination, samples from 19 animals were included. Platelet concentrates were prepared using a buffy coat method. Platelets, platelet-derived growth factor BB and transforming growth factor beta1 concentrations were increased in the concentrates compared to whole blood or serum (p < 0.05), while white blood cells were reduced (p < 0.05). The concentrates were lysed using freeze/thaw cycles, which eliminated the cells while growth factor concentrations were maintained. Donor age negatively correlated with platelet and growth factor concentrations after processing (p < 0.05). Finally, all lysates were pooled and the ePL was evaluated as culture medium supplement in comparison to FBS, using adipose-derived MSC from 4 unrelated donor horses. MSC proliferated well in 10% FBS as well as in 10% ePL. However, using 5% or 2.5% ePL entailed highly inconsistent proliferation or loss of proliferation, with significant differences in generation times and confluencies (p < 0.05). MSC expressed the surface antigens CD90, CD44 and CD29, but CD73 and CD105 detection was low in all culture media. Adipogenic and osteogenic differentiation led to similar results in MSC from different culture media. The buffy coat method is useful to produce equine platelet concentrate with increased platelet and reduced white blood cell content in large scales. The ePL obtained supports MSC expansion similar as FBS when used at the same concentration (10%). Further investigations into equine MSC functionality in culture with ePL should follow.